(untitled) (Research, Society and Development, 2022)
Crambe is a new crop that produces oil used for biodiesel production. Soil compaction in a no-tillage (NT) system is one of the main challenges for sustainable grain production in soil clay. The objective of this study was to evaluate the effect of compaction degree on crambe grain yield over two years. The levels of artificial compaction were generated using a roller compactor (0, 1, 3, and 5 passes) under a NT system. The experimental design was a strip block, and soil density and crambe grain yield were evaluated. The passes of the roller increased the density from 0.98 to 1.24 Mg m−3 in the 0–0.1 m layer, and 1.03 to 1.15 Mg m−3 in the 0.1–0.2 m layer. As a result, the compaction degree increased from 53% to 66% in the 0–0.1 m layer and 54% to 61% in the 0.1–0.2 m layer. Five passes of the roller compactor reduced the crambe grain yield by 41% and 9% in the first and second years, respectively, compared to the NT system without additional compaction. The crambe grain yield was reduced when the compaction degree reached 53%; therefore, crambe is not suitable for compacted soils.